Applicability of the field deformation measurement data in predicting the stability of embankment slopes - Nawarathna, T.H.K.; de Silva, L.I.N.; Kawasaki, Satoru (University of Jaffna, 2021)
Microbial induced carbonate precipitation (MICP) has gained much attention recently as an ecofriendly approach to treat the problematic grounds. In MICP, calcium carbonate (CaCO3) is produced artificially by hydrolysis of urea using enzyme urease. In the current research, the effect of the cationic polysaccharide, chitosan on the MICP process was investigated. CaCO3 precipitation experiment was conducted with and without chitosan by the hydrolysis of urea using ureolytic bacteria Pararhodobacter sp. SO1 in the presence of CaCl2. Morphology and the polymorphism of the samples were analyzed by scanning electron microscopy and X-ray diffraction. In the presence of chitosan, higher amount of precipitate was obtained than that of without chitosan. Without chitosan, rhombohedral crystals were dominant while with chitosan distorted crystal agglomerations combined with the chitosan hydrogel were observed. Further, sand solidification experiments were conducted in the presence and absence of chitosan. With chitosan, strongly cemented sand specimen could be obtained
Keywords: calcium carbonate; cementation; hydrogel; morphology